Consideration of urban green space in impact assessments for health. Issue 1 (2nd January 2018) - Fischer, Thomas B.; Jha-Thakur, Urmila; Fawcett, Peter; Clement, Sarah; Hayes, Samuel; Nowacki, Julia
Abstract: This paper explores how health aspects connected with the planning of urban green space are currently supported through two types of impact assessments: health impact assessment (HIA) and environmental assessment, including strategic environmental assessment (SEA) of policies, plans and programmes and environmental impact assessment (EIA) of projects. Seven HIAs and five EIAs/SEAs from the UK, the US, the Netherlands, Austria and Germany are reviewed, using an analytical framework designed on the basis of a literature review. An important finding is that whilst all HIAs follow a problem-/objectives-driven approach, designing guidelines for potential future projects, all EIAs/SEAs use an impact-driven approach, focusing on the impacts of planned and concrete action. HIAs therefore approach policy, plan, programme and project-making exercises from the outside, making suggestions to those working on them to consider certain aspects in the future, rather than working with them on improving things within a decision-making process, as is usually is usually the case with EIAs/SEAs.